APLIKASI E-VOTING UNTUK PEMILIHAN KETUA OSIS DI SMA XYZ BERBASIS WEB RESPONSIVE - Dahnial Dahnial (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2020)
Student council election is a routine school activity every year, but currently the student council election is done manually using ballot papers containing the candidates. The weakness of this system is in addition to the process of getting longer results, it is also prone to fraud due to the excess of manipulated ballot papers, as well as being less environmentally friendly. Therefore the need for a system that is able to provide solutions to these problems, one of which is a responsive web-based student council election system. Web-based systems are more common than mobile-based systems, because they are supported by all device platforms, different if only based on mobile (Android), only devices based on the Android operating system can use the application. Moreover, web technology is now very good, responsive web allows the display of web pages to adjust to the user's screen size automatically, responsive web framework used in this study is bootstrap. In this study, researchers used a software development model which is a prototype. And for the tools used in developing this application is the Unified Modeling Language, and the system testing method uses a blackbox. The results of this study are expected to provide results in the form of a system that is fast and accurate, cost effective and environmentally friendly. Keywords: e-voting, bootstrap, prototype